PROSES PENGIMBUHAN DALAM BAHASA BIDAYUH-SOMU: MORFEM NOMINAL - Bunau, E (Jurnal Kajian Pembelajaran dan Keilmuan, 2018)
AbstractThis research is aimed to identify and describe morphemes and allomorphs applied in nominal affixation process of Bidayuh-Somu Language. The research is field linguistics implementing recording technique to collect the data. Utterances containing nominal morphemes and allomorphs were collected from the language speaker informants and sorted accordingly to word class. The research found that the nominal morphemes of the language is both class-maintaining and class-changing. To form word, the nominal morpheme is affixed to nouns, verbs, and numbers. The nominal morpheme of Bidayuh-Somu Language comprises prefix, infix, and circumfix.     Key words: affixation process, morpheme, allomorph, class-maintainng and             class-changing.